Evaluation Sustainability Agriculture Precision Based Robotics and Sensors against Efficiency Use Source Water Power - Aulia Rizki (Digital Agriculture and Innovation Journal, 2025)
Agriculture precision become solution strategic in face challenge efficiency use source water resources in the sector agriculture , especially in tropical areas that are prone to water crisis . Research This aim evaluate sustainability system agriculture precision based deep robotics and sensors increase water efficiency . Research done with approach qualitative studies cases in two location agriculture tropical which has apply system precision based on humidity , weather and irrigation sensors automatic . Data collection techniques are carried out through interviews , observations field , and sensor documentation , then analyzed in a way thematic . The results show decline irrigation water consumption up to 42%, an increase accuracy water distribution , as well as subtraction burden manual work . System this is also accepted good by farmers after through stages training and adaptation . Implications study This push development technology agriculture efficient , adaptive , and sustainable precision in water management in an era of change climate .